Secondary prevention of coronary artery disease: a retrospective observational analysis of italian healthcare administrative data. (11th May 2022) - Calabria, S; Piccinni, C; Ronconi, G; Dondi, L; Cinconze, E; Pedrini, A; Esposito, I; Addesi, A; Martini, N; Maggioni, AP
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): ACARPIA Farmaceutici S.r.l. Background/Introduction: Prevalence and mortality rates in patients with a documented coronary artery disease (CAD) are high, mainly due to the suboptimal adherence to the recommendations of current guidelines on secondary prevention strategies. Purpose: This study aimed to describe patients with CAD and eligible to secondary prevention and assess their 1-year healthcare resource consumption and costs, from the perspective of the Italian National Health Service (INHS). Methods: From our database of Italian healthcare administrative data, reliably representative of the whole Italian population, a cross-linkage of demographics, hospital discharges and exemption code for disease cost sharing, through a unique anonymized identifying code, was performed. Patients aged ≥35 in 2018 (accrual period) with CAD (index date) and eligible to secondary prevention (by excluding subjects with end-stage kidney disease/neoplasia) were selected. They were characterized in terms of age, gender and comorbidities (from index date back to 2015) and followed for 1 year to assess drug consumption, hospitalizations and healthcare integrated costs. Results: Out of >5 million inhabitants in the database in 2018, 46, 063 patients aged ≥35 (1.3%) with CAD and eligible for secondary prevention were selected (72.1% males; mean age [±SD] 70±12). About half of them had 3 or more comorbidities of interest: mostly hypertension (90%), dyslipidaemia (72%) and diabetes (33%). During 1-year follow-up, at least one drug for secondary prevention was supplied to 96.4% of patients: mainly antiplatelets (83%), lipid lowering agents (83%) and β-blockers (73%). At the same time, 95.8% of the cohort was treated with at least one non-cardiovascular drug. The 30.6% of subjects were hospitalized at least once: 11.4% due to relevant cardiovascular causes (mostly acute coronary syndrome and heart failure), 9.1% due to other cardiovascular events and 17.5% because of non-cardiovascular events. On average, the INHS yearly paid €6, 078 per patient: hospitalizations accounted for the 70% of the whole expenditure. Conclusions: This study showed an integrated view of the relevant burden of CAD for patients and the INHS. A multidisciplinary and a more adherent approach to current guidelines are compelling to improve patients' outcomes and reduce costs for the INHS.